2021
DOI: 10.1002/jat.4253
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fentanyl toxicity and metabolism using a zebrafish model

Abstract: The increased abuse of novel drugs has created a critical need for cheap and rapid in vivo models to understand whole organism drug‐induced toxicity and metabolic impacts. One such model is zebrafish, which share many similarities to human. Assays have been developed for behavioral, toxicity, and metabolism elucidation following chemical exposure. The zebrafish model provides the advantage of assessing these parameters within a single study. Previous zebrafish studies have evaluated the behavioral effects of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…In particular, 100% of larvae exposed to fentanyl 50 and 100 μM showed an abnormal pericardial edema (PE), yolk sac edema (YSE), jaw defect (J) and spinal curvature (SC), as shown in Figure 1. These malformations have already been highlighted for fentanyl, 18,19 other fentanyl analogs, 16 cannabinoids 20 and environmental toxins. 21 Furthermore, at those concentrations, larvae seemed to be sedated and suffering, consequently it was decided to reduce the drug concentrations to 10 μM (which induces malformations only in 1/3 of cases) and 1 μM (that caused no malformations) for further experiments.…”
Section: Maximum-tolerated Concentrations (Mtc) In Zebrafish Larvae: ...mentioning
confidence: 92%
“…In particular, 100% of larvae exposed to fentanyl 50 and 100 μM showed an abnormal pericardial edema (PE), yolk sac edema (YSE), jaw defect (J) and spinal curvature (SC), as shown in Figure 1. These malformations have already been highlighted for fentanyl, 18,19 other fentanyl analogs, 16 cannabinoids 20 and environmental toxins. 21 Furthermore, at those concentrations, larvae seemed to be sedated and suffering, consequently it was decided to reduce the drug concentrations to 10 μM (which induces malformations only in 1/3 of cases) and 1 μM (that caused no malformations) for further experiments.…”
Section: Maximum-tolerated Concentrations (Mtc) In Zebrafish Larvae: ...mentioning
confidence: 92%
“…Studies have been performed to investigate metabolite markers for synthetic cannabinoids, 19 human performance‐enhancing drugs, 20,21 synthetic cathinones, 22 and opioids 23,24 using the zebrafish model. More recently, we utilized the zebrafish model as a single assay for the toxicity and metabolism of fentanyl and detected norfentanyl, β‐hydroxyfentanyl, and 4‐anilino‐ N ‐phenethylpiperidine (4‐ANPP) from 24 to 96 h postfertilization, 25 providing additional support for their ability to metabolize opioids.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we utilized the zebrafish model as a single assay for the toxicity and metabolism of fentanyl and detected norfentanyl, β-hydroxyfentanyl, and 4-anilino-N-phenethylpiperidine (4-ANPP) from 24 to 96 h postfertilization, 25 providing additional support for their ability to metabolize opioids.…”
mentioning
confidence: 99%
“…Compared to rodent models, zebrafish models require less space for behavioral testing, less expenditure on experimental individuals, and less requirements for animal welfare. It was found that the fentanyl metabolic pathway in zebrafish was similar to that of rats, implying that toxicity results from zebrafish could be verified by other models [ 18 ]. In addition, zebrafish larvae have been used to validate cardiotoxicity due to fentanyl exposure [ 19 ] and respiratory depression toxicity [ 20 ].…”
Section: Introductionmentioning
confidence: 99%